Współpraca przedsiębiorstw uzdrowiskowych z gminami - Januszewska, Małgorzata (Cooperation of Spa Enterprises with Communes, 2005)
Cooperation of local self-government, representing a spa type of commune, with spa enterprises functioning in its area, becomes an indispensable condition for further development of both its treatment and tourist function. The objective of the hereby article is an attempt to evaluate such cooperation from the point of view of spa enterprises' representatives. An institutional platform for such cooperation, its barriers and the scope for its activities, have been presented on the basis of the conducted research in the form of a survey.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 162-180